Digital mammography : characterisation of practice and equipment performance in portuguese healthcare providers - Reis, Cláudia Isabel Sá dos (2013)
Mammography is a key imaging modality used in screening and front line diagnosis of breast disease. Digital imaging systems for mammography were introduced in the 1980´s and since then they have been replacing the conventional analogue (screen-film) systems. The adequate clinical performance of digital mammography has been validated in extensive trials and the modality gained popularity and is currently in clinical use worldwide. The successful transition from screen-film to digital mammography and the cost-effective use of the digital technology requires a clear understanding of the potentials and limitations of digital imaging systems and the impacts on established workload and workflow routines. The adoption of optimised practices in digital mammography is a critical step to produce images with adequate diagnostic quality whilst keeping the radiation dose (and associated risk to the patient) to the minimum necessary. Digital mammography was introduced in Portugal in 2000 and currently is in use in various hospitals and clinics for screening, diagnostic and intervention. However, the existing literature is limited and obsolete and does not allow a clear, and independent, perspective of the level of innovation in mammography in Portugal nor the quality of mammography services provided to the patient. This research investigates: the level of innovation in mammography in Portugal, the practices in use with focus on the technology and technical performance of digital mammography systems installed in Portuguese healthcare providers. In addition, compliance with international quality standards for mammography is assessed and, where appropriate, recommendations are provided to improve current practice. An extensive search was performed in governmental bodies, healthcare providers and industry to map the installed base of mammography technology in Portugal. A survey to healthcare providers was undertaken to capture data on the practices in use for mammography in hospitals and clinics. A comprehensive technical protocol was developed for assessing the performance of digital mammography systems. The existing guidance European Reference Organisation for Quality Assured Breast Screening and Diagnostic Services (EUREF), International Atomic Energy Agency (IAEA), Institute of Physics and Engineering in Medicine (IPEM) and National Healthcare Service Breast Screening Program (NHSBSP) were considered. This protocol was applied to a sample (52) of digital mammography systems in current use in hospitals and clinics in Portugal and included tests to the performance of the X-ray source and to the image receptor. A total of 446 mammography systems were identified in Portugal (including conventional and digital technology) with the vast majority (76%) installed in private healthcare centers. The equipment age in clinical use varied noticeably ranging from legacy to state of the art equipment. The majority of mammography systems (64%) are computed radiography (CR) imaging technology based on a photostimuable phosphor image receptor (image plate) and an associated optical processor. The number of direct digital mammography systems (DR) is relevant (67) and has been gradually increasing. Two state of the art mammography systems with tomosynthesis capabilities were identified. Sixty five healthcare providers participated in the survey to map practices in digital mammography. The survey showed that the selection of exposure settings in digital mammography equipment is most frequently driven by the recommendations of the manufacturers. A limited number of centers (26%) stated using international guidelines as reference. The use of protocols developed locally was rarely reported. A routine quality control (QC) programme is in place in 70% of the participants’ centers and it is undertaken most frequently under an outsourcing contract by external QC providers. The support of a local medical physicist/engineer for QC and optimization activities is rare in the participant centers. The vast majority (76%) of radiographers participating in the survey does not perform periodic analysis of rejected (and repeated) mammography images, despite this being a simple and important QC task. Radiographers and radiologists involved in mammography reported training needs in digital mammography. Radiographers would welcome training in artifact recognition, quality control and dosimetry. Radiologists named training needs also in artifact recognition and quality control and, additionally, in breast pathology. The majority (97%) of radiologists agrees with the need to implement a program for certification of mammography in Portugal and would adhere to a voluntary program. Arguments presented were that certification could bring necessary improvements in staff training whilst contributing to maintain equipment performance and staff practices at adequate levels. In addition certification could promote quality and harmonization of mammography practice nationwide. The technical assessment of the mammography systems showed a very wide range of performance across the various systems. The performance of the X-ray system (tube and generator) was generally very good for most systems. The tube output was accurate and reproducible across the range of clinically relevant tube voltage (kVp) and tube charge (mAs) settings. A very large proportion of mammography systems tested (70%) showed misalignment between the light and radiation fields. For 8 systems the misalignment is causing unnecessary irradiation beyond the breast anatomy towards the patient chest wall and lungs. The majority of image receptors (83% CR and 93% DR) showed good uniformity. Artifacts were observed on various CR image plates some of which pose the risk to compromise the visibility of clinically relevant details. These were due to dust in the phosphor, damaged phosphor due to extensive use and aging, and mechanical stress during processing. Measurements of Signal-difference to Noise Ratio (SdNR) for typical clinical settings (AEC) were performed for various breast thicknesses (mimicked with slabs of Perspex). For DR systems the vast majority of results obtained were within the recommended reference values (IAEA) with exceptions observed for the larger breast thicknesses. For CR systems the mean values of SdNR were frequently lower than the reference values suggesting a possible miscalibration of the AEC system or limited contrast performance of the image receptor. SdNR should be assessed regularly as it is an important objective metric of the performance of the image receptor and has an impact in image contrast. The mean glandular dose (MGD) was measured on a standard Perspex phantom (45 mm) for each system using the method proposed by Dance et al. In addition MGD was measured in realistic (clinical) conditions using exposure settings collected from mammography examinations. Dose reference levels (DRL) were determined using the 75th percentile of the MGD distributions. For both measurements with Perspex and using clinical exposures, the average MGD for CR systems was higher compared to the DR systems. The average MGD in phantom (considering both technologies) is within the acceptable reference range proposed by EUREF (< 2.5 mGy). The mean MGD for the mediolateral oblique (MLO) projection was higher than for the craniocaudal (CC) projection. For CR systems the results are 1.85 mGy (CC projection) and 2.10 mGy (MLO projection). For DR systems the corresponding values are 1.54 mGy (CC) and 1.68 mGy (MLO). The DRL (clinical) is 2.2 mGy and 1.5 mGy for CR and DR systems, respectively. The DRL (phantom) is 2.0 mGy and 1.2 mGy for CR and DR systems, respectively. The technical image quality (IQ) performance was assessed with images produced with a breast phantom (TORMAM). Approximately 200 images were acquired and analysed visually by 4 trained observers on a calibrated high-resolution electronic display. The analysis consisted on the identification of low contrast detail detectability thresholds for structures in the phantom image that mimic breast abnormalities (spicules, nodules, clusters of micro-calcifications). An overall average score was calculated for each image and used as a metric of image quality. A wider range of IQ scores was observed for CR mammography systems (30-100) compared to DR systems (61-91) showing wider variations in image quality between systems. The 75th percentile of the score distribution was score=70 for CR and score=85 for DR revealing a lower IQ performance of CR systems compared to DR systems. A small but important number of mammography systems (8 CR and 4 DR) showed very poor technical IQ performance (percentile 25th) and require further investigation. For both technologies higher IQ scores were most frequently associated with higher MGD values with some exceptions observed. For comparative IQ scores the MGD is higher for CR systems compared to DR systems showing improved dose efficiency of the DR technology. The research has documented important data and conclusions regarding the installed base of mammography equipment in Portugal, current practices and technical performance of mammography systems in clinical use. The need of dedicated training in mammography was highlighted by radiologists and radiographers involved in mammography. The study provides a background to all stakeholders for planning improvements to mammography departments.